Studi Komparatif Terhadap Makna Itab Kepada Nabi Muhammad Dalam Perspektif Sayyid Quthub dan Buya Hamka - Farid Fauzi; Risman Bustamam; Edriagus Saputra (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Itab is a term used to commemorate and reprimand the Prophet Muhammad when he made a mistake, but in the interpretation of Fiy Zhilalil Qur'an by Sayyid Al-Quthb and Tafsir Al-Azhar by Buya Hamka, they differ in interpreting the word itab contained in the verses. Al-Qur'an. The purpose of this study is to analyze the differences in interpreting the word itab contained in the Qur'an and in this study the author focuses on the verses that explain the sour face and turn away and forbid something that is lawful. This study uses a qualitative method with a library research model and compares the interpretations of Sayyid Qutb and Buya Hamka. From the results of this study which discusses Itab to the Prophet Muhammad SAW, that the two interpreters differ in explaining the meaning of Itab: in terms of language, Sayyid Qutb divides it into 2 types, namely Hard and Soft, while Buya Hamka only has 1 type, namely soft. In terms of terms, Sayyid Qutb uses 2 terms, namely itab and tazdkirah (warning), while buya Hamka uses the terms itab, warning and reprimand. In terms of his position, Sayyid Qutb said that this was a warning to the Prophet Muhammad because of his mistake in ijtihad, so that it had an impact on Islamic law, while according to Buya Hamka, the error of the Prophet Muhammad in ijtihad had no impact on Islamic law, because the Prophet SAW could not be separated from the side of the Prophet Muhammad. mistakes as ordinary people. According to Sayyid Qutb, not all Itabs were addressed to the Prophet Muhammad, but some were addressed to Muslims, while according to Buya Hamka, the Itabs were only addressed to the Prophet Muhammad.